High-performance cycling - Jeukendrup, Asker E., 1969- (Champaign, IL : Human Kinetics, 2002)
For both cyclists and cycling coaches, experts from all over the world present cutting-edge information on performance assessment, body positioning, equipment, nutrition, endurance, strength and injury prevention that can be used immediately for training and racing success
Includes bibliographical references (pages 285-298) and index.
Keywords: Cycling -- Training